Pengaruh Model Pembelajaran Personalized System of Instruction (PSI) dalam Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa SMA - B Erdiansyah Putra; Ika Wirahmad; Gunawan Gunawan (SUPERMAT : Jurnal Pendidikan Matematika, 2021)
This research is motivated by the low activity and learning outcomes of students in one of the public high schools in Bima City. The purpose of this research is to increase students' activities and learning outcomes of mathematics by applying Personalized System of Instruction (PSI) learning. The type of research used in this study is quasi-experimental, it is said that because in this design the researcher cannot control all external variables, namely external factors that are not examined and become a nuisance so that it affects the course of the experiment. The results of this study indicate that all aspects that are assessed appear during the learning process. This is complemented by the results of statistical tests with the results of tcount greater than ttable, namely 2.86 > 1.67 with the acquisition of the average value of learning outcomes in the experimental class which is greater than the control class, which is 65.8 > 53.9. This means that the Personalized System of Instruction (PSI) learning model gives better results than conventional learning. Thus, the steps of the PSI learning model have an influence in increasing students' activities and learning outcomes in mathematics.